Review of the Gasteruptiidae (Hymenoptera: Evanioidea) from the territory of the former Yugoslavia, with three newly reported species - Žikić, Vladimir; Achterberg, Cornelis Van; Stanković, Saša S.; Dubaić, Jovana Bila; Ćetković, Aleksandar (Zootaxa, 2014)
The results of more than 120 years of investigation of the fauna of Gasteruptiidae for the territory of former Yugoslavia (including Bosnia and Herzegovina, Croatia, FYR of Macedonia, Montenegro, Serbia and Slovenia) are summarized. Results from recently collected material and from unidentified specimens in collections are combined with those of published records. The total number of valid species of the genus Gasteruption Latreille for the area of former Yugoslavia is 22, which is more than in any country represented in Fauna Europaea database. One species is firstly recorded for the mainland Europe (G. syriacum Szépligeti), two more species are newly recorded for the investigated area and there are 23 first country-records for the involved countries (based on 17 species).